Idiopathic Spontaneous Adrenal Hemorrhage in the Third Trimester of Pregnancy - Narin Nasiroglu Imga; Yasemin Tutuncu; Mazhar Muslum Tuna; Berçem Ayçıçek Doğan; Dilek Berker; Serdar Guler (Case Reports in Medicine)
Spontaneous adrenal hemorrhage (SAH) is seen in the absence of trauma or adrenal tumor in adrenal glands. The incidence of SAH has been reported from 0.14% to 1.1% and it usually involves the right gland. During pregnancy, idiopathic unilateral SAH has been reported rarely. We present a case which comes to emergency department with an acute abdominal pain and the test results showed spontaneous left SAH.